Komunikasi Bisnis PT Galih Estetika Indonesia dalam Meningkatkan Kemitraan Ubi Jalar - Luthfi Nur’azkiya; Lukman Mohammad Baga; Netti Tinaprilla (Institut Pertanian Bogor, 2017)
PT Galih Estetika Indonesia is a first sweet potato agroindustry company in Indonesia that produces sweet potato paste products by export scale. The increasing demand causes companies to establish partnerships with farmers to meet the needs of raw sweet potatoes as input for production. In establishing partnerships it takes good communication to create relationships that can be used to solve all existing business problems. By using all forms of communication both verbal and nonverbal, then communication can be directed to achieve certain goals. The purpose of this research is to describe picture of partnership and partnership pattern which run by PT Galih Estetika Indonesia and analyze business communication conducted by PT Galih Estetika Indonesia in improving sweet potato partnership. This research uses qualitative descriptive method with data collection technique through in-depth interview, FGD (Focus Group Discussion), and observation. The result of this research shows that the partnership has not run optimally and the communication done by PT Galih Estetika Indonesia does not necessarily only communicate, but also keeps the communication in order not to break, so the business relationship can continue that will impact on the profit earned by the company . Well-established communication able to overcome all problems of raw material availability. All forms of conflict can be resolved by business communication.